KEY SUCCESS FACTORS OF WOMEN'S MSMEs IN DEPOK CITY - Suharyati, Suharyati; Nobelson, Nobelson (Kesatuan Press, 2025)
This study aims to identify the key success factors for women’s MSMEs in Depok City by analyzing data from 120 women-owned MSMEs. Women’s MSMEs in Indonesia are a crucial pillar of the local economy, contributing significantly to poverty alleviation, job creation, and family economic empowerment. Using quantitative methods, the study employs Principal Component Analysis (PCA) with varimax rotation. Out of the 29 variables initially studied, they were grouped into seven main components. The results indicate that the 29 variables were reduced to 16, which were categorized into seven key components: business environment and opportunities, digital independence and technology, marketing communication and financial literacy, financial capabilities, and virtual networks, adaptive strategies and entrepreneurial efficiency, government support and competitive advantage, and entrepreneurial skills and digital marketing. These components offer a comprehensive understanding of the critical success factors for women's MSMEs. This study provides strategic recommendations for women’s MSME and the government, particularly the Depok City Cooperative and MSME Service, to formulate policies that promote women’s economic empowerment in the MSME sector.